Conducting research in psychology : measuring the weight of smoke - Pelham, Brett W.; Blanton, Heart (Belmont, California : Wadsworth, Cengage Learning, 2013)
Includes hands-on activities that involve learning by doing, methodology exercises that encourage students to use their intuition to understand research methods, and methodology problems that teach students to apply basic research principles to novel problems.
1. How Do We Know? 2. How Do We Find Out? The Logic, Art, and Ethics of Scientific Discovery. 3. Moving from Fact to Truth: Validity, Reliability, and Measurement. 4. Moving from Notions to Numbers: Psychological Measurement. 5. How Do We Misinterpret? Common Threats to Validity. 6. Nonexperimental Research Designs. 7. Experience Carefully Planned: Experimental Research Designs. 8. Experience Carefully Exploited: Quasi-Experimental Research Designs. 9. Choosing the Right Research Design. 10. A Brief Course in Statistics. 11. Telling the World About It. 12. Putting It All Together: Maximizing Validity with Multi-Method (and Highly Creative) Research. 13. Putting Your Knowledge to Work
Includes bibliographical references.
Keywords: PSYCHOLOGY -- RESEARCH -- METHODOLOGY